2007
DOI: 10.1007/s11104-007-9343-0
|View full text |Cite
|
Sign up to set email alerts
|

Copper uptake and phytotoxicity as assessed in situ for durum wheat (Triticum turgidum durum L.) cultivated in Cu-contaminated, former vineyard soils

Abstract: This work assessed in situ, copper (Cu) uptake and phytotoxicity for durum wheat (Triticum turgidum durum L.) cropped in a range of Cucontaminated, former vineyard soils (pH 4.2-7.8 and total Cu concentration 32-1,030 mg Cu kg −1 ) and identified the underlying soil chemical properties and related root-induced chemical changes in the rhizosphere. Copper concentrations in plants were significantly and positively correlated to soil Cu concentration (total and EDTA). In addition, Cu concentration in roots which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
81
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(105 citation statements)
references
References 36 publications
12
81
1
4
Order By: Relevance
“…This might be related to the method that we used for measuring Cu availability. Michaud et al (2007) have shown that in calcareous soils contaminated by Cu fungicides, water-extractable Cu varied little, compared to total soil Cu, or EDTA-extractable Cu.…”
Section: Effects Of Organic Farming On Soil Organismsmentioning
confidence: 99%
“…This might be related to the method that we used for measuring Cu availability. Michaud et al (2007) have shown that in calcareous soils contaminated by Cu fungicides, water-extractable Cu varied little, compared to total soil Cu, or EDTA-extractable Cu.…”
Section: Effects Of Organic Farming On Soil Organismsmentioning
confidence: 99%
“…L'origine de cet élément dans les eaux souterraines serait le résultat des applications agricoles (engrais, pesticides et autres dérivés cuivreux : DUmESTRE et al, 1999;KOmAREK et al, 2009;miCHAUD et al, 2007). La concentration du Cu dans l'eau est influencée par la taille des grains des engrais contenant cet élément, du temps de séjour et de l'humidité de sol (PETERSEN et al, 2004).…”
Section: Métaux Lourds Dans Les Eaux De La Nappeunclassified
“…Heavy metal contamination in soil is a major problem for the environmental quality of the world (Yoon et al 2006). Copper is an essential nutrient for plant growth at low concentrations, but excessive amounts are phytotoxic (Michaud et al 2007).…”
Section: Introductionmentioning
confidence: 99%